Parents Seeking Health-Related Information on the Internet: Cross-Sectional Study - Bianco, Aida; Zucco, Rossella; Nobile, Carmelo Giuseppe A; Pileggi, Claudia; Pavia, Maria (JMIR Publications, 2013)
BackgroundThe Internet represents an increasingly common source of health-related information, and it has facilitated a wide range of interactions between people and the health care delivery system. ObjectiveTo establish the extent of Internet access and use to gather information about health topics and the potential implications to health care among the adult population in Calabria region, Italy. MethodsThis cross-sectional study was conducted from April to June 2012. The sample consisted of 1544 adults aged ≥18 years selected among parents of public school students in the geographic area of Catanzaro in southern Italy. A 2-stage sample design was planned. A letter summarizing the purpose of the study, an informed consent form, and a questionnaire were given to selected student to deliver to their parents. The final survey was formulated in 5 sections: (1) sociodemographic characteristics, (2) information about chronic diseases and main sources of health care information, (3) information about Internet use, (4) data about the effects of using the Internet to search for health information, and (5) knowledge and use of social networks. ResultsA total of 1039 parents completed the questionnaire, with a response rate equivalent to 67.29%. Regarding health-related information types, 84.7% of respondents used the Internet to search for their own medical conditions or those of family members or relatives, 40.7% of parents reported looking for diet, body weight, or physical activity information, 29.6% searched for vaccines, 28.5% for screening programs, and 16.5% for smoking cessation tools and products. The results of the multiple logistic regression analysis showed that parents who looked for health-related information on the Internet were more likely to be female (OR 1.53, 95% CI 1.05-2.25), with a high school diploma (OR 1.69, 95% CI 1.02-2.81) or college degree (OR 2.14, 95% CI 1.21-3.78), younger aged (OR 0.96, 95% CI 0.94-0.99), with chronic conditions (OR 1.94, 95% CI 1.17-3.19), not satisfied with their general practitioner's health-related information (OR 0.6, 95% CI 0.38-0.97), but satisfied with information from scientific journals (OR 1.99, 95% CI 1.33-2.98). ConclusionsOur analyses provide important insights into Internet use and health information-seeking behaviors of the Italian population and contribute to the evidence base for health communication planning. Health and public health professionals should educate the public about acquiring health information online and how to critically appraise it, and provide tools to navigate to the highest-quality information. The challenge to public health practice is to facilitate the health-promoting use of the Web among consumers in conjunction with their health care providers.